Review: Biogas Fermentation Process - Mohammad Arriza Novan Tahta Aunillah; Bintang Bayu Cezarridfalah; Erwan Adi Saputro; Noor Ariefandie Febrianto (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Biogas is a gas generated through anaerobic processes that involve the decomposition of organic materials. Various sources of methane can be utilized to produce biogas, including household waste, biodegradable waste, animal waste, or organic materials that can break down under anaerobic conditions. The objective of this study is to investigate how different conditions, such as time, pH levels, stirring duration, and the type and concentration of inoculum, influence biogas production, with the aim of identifying the optimal conditions for the biogas production process. This research focused on examining the factors that impact the biogas production process, which includes several stages like hydrolysis, acetogenesis, acidogenesis, and methanogenesis. The findings from prior experiments showed that the optimal biogas production was achieved using tofu liquid waste, resulting in a volume of 26,700 ml over a 36-day period. This was achieved by maintaining an operating temperature between 35-40°C and employing cow dung as the inoculum, along with a 36-liter digester.